2008
DOI: 10.1007/s11182-008-9062-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations and computer simulations of the intergrain diffusion in submicro-and nanocrystalline metals

Abstract: Investigations of the features of the diffusion along grain boundaries and of the diffusion-controlled processes in submicroscopic and nanocrystalline materials produced by methods of intense plastic deformation are reviewed. To determine the parameters of the diffusion along grain boundaries and triple junctions in metals, which are independent of the results of processing of diffusion experiments based on diffusion models, results of a molecular dynamic investigation of the diffusion in nanocrystalline coppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Here we assume that the triple junction area is a homogeneous phase Grain Boundary Diffusion, Stresses and Segregation in the form of a cylinder of radius R [1]. Assuming that the shrinkage of grain boundary δA is equal to nRl TJ , using (1) and stereometrical identity we derive equation for calculating ζ GB and ζ TJ [4]:…”
Section: Methodsmentioning
confidence: 99%
“…Here we assume that the triple junction area is a homogeneous phase Grain Boundary Diffusion, Stresses and Segregation in the form of a cylinder of radius R [1]. Assuming that the shrinkage of grain boundary δA is equal to nRl TJ , using (1) and stereometrical identity we derive equation for calculating ζ GB and ζ TJ [4]:…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, some fundamental, usually structure-insensitive properties of these materials, such as the elastic modulus, Curie and Debye temperatures, specific heat, etc., are varied [3]. It has been revealed that for SMC and NS metals produced by plastic deformation the grain-boundary diffusion coefficients are several orders of magnitude greater compared to those for individual GBs in bicrystals or GBs in coarse-grained polycrystals [13][14][15][16][17][18][19]. The increased diffusion coefficient for the state under discussion makes the structure highly sensitivitve to the action of the environment.…”
Section: Features Of Diffusion and Diffusion-controlled Processes In mentioning
confidence: 99%
“…Experimental investigations on this line are difficult in view of the small size of structure elements and of the atomic scale of the processes involved. The same circumstance necessitates the study of the mechanisms of diffusion-controlled processes in NC materials by methods of computer simulation at the atomic level [16]. Investigations at this level form a basis for developing models which would allow one to predict the behaviour of NC materials by using the methodology of multiscale simulation of materials and processes [9] in combination with methods of mesomechanics [32].…”
Section: Features Of Diffusion and Diffusion-controlled Processes In mentioning
confidence: 99%
See 1 more Smart Citation